Diurnal Variation of the Peripheral Cholinergic Antiinflammatory Function in Mice. (16th June 2016) - Fan, Bo‐Shi; Zhang, En‐Hui; Cheng, Ming‐He; Wu, Zhao‐Tang; Han, Bing; Yu, Jian‐Guang
Summary: Aims: Cholinergic antiinflammatory (CAI) pathway functions importantly in inflammation via α7 nicotinic acetylcholine receptors (α7nAChR). The present work tested circadian rhythm in peripheral CAI activity and validities of CAI activity and glucocorticoids in chronotherapy for lipopolysaccharide (LPS)‐induced shock. Methods: Vesicular acetylcholine transporter (VAChT) expressed in liver and kidney was examined every 3 h in C57BL/6 mice. Proinflammatory cytokines in serum and survival time in shock were monitored after LPS injection every 3 h. Mifepristone, antagonist of glucocorticoid receptors, and methyllycaconitine (MLA), antagonist of α7nAChR, were administrated before LPS to block antiinflammatory function of endogenous glucocorticoids and acetylcholine. Results: Both levels of tumor necrosis factor α, interleukin 1β, and interleukin 6 and mortality exhibited diurnal variations with prominent peaks when LPS was given at 15:00, and the minimum mortality occurred at 00:00. Expression of VAChT increased during resting period. MLA increased serum proinflammatory cytokines slightly, but not affected survival rate. Both differences in cytokines and in survival times between LPS injection at 15:00 and 00:00 were eliminated by mifepristone, but not by MLA. Conclusion: Peripheral CAI pathway exerts more powerful antiinflammatory effect during resting period. Glucocorticoids appear to be efficient in chronotherapy for septic shock.